Development and performance tests of a separator for removal of physically emulsified and free oils from wastewaters - Law, Puong Ling, Dr.; Ngu, Lock Hei; Wong, Kien Kuok; Awangku Abdul Rahman, Pgn. Hj. Yusof, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/